(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The cultural development of India amid the British period. "Culture" is a difficult word to characterize, however I have taken it in the broadest sense, to incorporate every one of those developments which need to do with a people’s psyche and its social organisation. Manners and morals, journalism and literature, education and public life, the change of religious and social thoughts, economics, craftsmanship and industry, lastly, politics in so far as they manage developmental thoughts as opposed to dubious certainties, will all claim our consideration. Be that as it may, every one of these issues must be put in due extent. Here we are not composing political or scholarly or religious or social history, or the history of education or journalism, workmanship, economics, or industry. We are taking a bird’s-eye perspective of the powers which are forming our culture.